APPLICATION OF THE ANALYTICAL HIERARCHY PROCESS (AHP) METHOD IN EMPLOYEE REWARDS DECISION MAKING - Syah, Bayu Erdian; Achsa, Andhatu; Ikhwan, Khairul (Faculty of Economics and Business University of Lampung, 2023)
This research aims to formulate a method to help make reward decisions through a UD Restu Bunda MSMEs case study. MSMEs are businesses in the creative economy that can withstand the shocks of uncertain economic conditions. Strong ambition to develop a business backfires because many things are often neglected. The bigger a business is, the more complex the management system is, one of which is rewards management. Rewards are employee appreciation based on criteria. Although no regulations state that business owners are required to provide rewards, giving rewards can also trigger internal conflicts, especially for MSMEs that do not have a structured and rational reward system. This research used the Analytical Hierarchy Process (AHP), which combines Expert Choice 11 (EC 11) and Microsoft Excel tools. The results of this research are mainly in formula development, where the modification is the discovery of a performance value coefficient that functions to maintain the exchange rate of the performance assessment score against the funds provided. The exchange rate will not change as long as there is no change in the number of employees and funds to prevent cost overruns. Based on simulations conducted at UD Restu Bunda MSMEs, it was found that four important aspects must be given more attention when conducting performance appraisals, namely loyalty, work quality, communication, and discipline. Keywords: Rewards Management; Rewards; SMEs; Analytic Hierarchy Process, Expert Choice 11